"Over 1000 Cars and No Garage": How Urban Planning Supports Car(Park) Sharing. Issue 3 (2nd July 2016) - Kent, Jennifer L.; Dowling, Robyn
Abstract: Car sharing programs demonstrate some success in efforts to challenge private car use by reducing private car ownership and personal vehicle kilometres travelled by private car. The relationship between what local urban planners "do" and car sharing has, to date, been relatively informal and undocumented. Yet urban planning will be integral to the ongoing success of car sharing. This paper first documents the relationship between urban planning and car sharing. It proceeds to review policy and practice to examine the way urban planning and car sharing interact in Australia's largest city, Sydney. The allocation of land to be used to park shared cars is highlighted as a key area of intersection. Our review reveals the emergence of several different approaches to the provision of car sharing parking, with parking-related policy used to both restrict and encourage the use of shared cars. While it is too soon to undertake a formal evaluation of the effectiveness of these approaches, this review provides a valuable snapshot of planning policy and practice concerning this quietly successful sustainable transport mode. It concludes by predicting a number of issues associated with the strategies employed, and positions these issues within wider debates on planning.